Pengaruh konservatisme terhadap efisiensi investasi dan agency cost sebagai variabel moderasi pada perusahaan yang melakukan merger dan akuisisi di asia tenggara - Juliani, Dina; Wardhani, Ratna (Jurnal Akuntansi, 2018)
This research aim to exmine the effect conservatisme on investment efficiency and agency cost as moderating variable. This research is conducted on public companies doing megers and acquisitions in Indonesia, Singapore, Malaysia, Vietnam, Philippines and Thailand from 2012-2016. The results show that conservatism has a positive effect on investment efficiency and agency cost strengthens the positive influence of conservatism on investment efficiency